(untitled) (Research, Society and Development, 2022)
The choice of cultivars is an important factor for greater productivity in agriculture. The objective of this work is to know the morphophysiological and developmental parameters of soybean cultivars. The experiment was conducted in August 2021, at Faculdades Integradas Stella Maris (FISMA), located in the Municipality of Andradina, State of São Paulo. The design was completely randomized, where five soybean varieties were grown: 8579R5F; 84I86; M8644IPRO; DM80I79; 81I81 and with four replicates, totaling 20 plots or pots. The cultivar 8579R5F stood out in the development parameters in number of trifoliate (NT), shoot dry mass (DMAP) and also in the concentrations of chlorophylls A and B. The cultivar M8644IPRO showed the highest internal leaf morphology parameters for phloem diameter (PD) and palisade parenchyma thickness (PPT). Chlorophyll A and B concentrations present correlations with positive linear responses with shoot dry mass. Stomatal functionality (SF) and phloem diameter (PD) present correlations with positive linear responses with adaxial epidermis thickness (ADET).